2020
DOI: 10.1186/s41610-020-00167-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of roadkill during breeding migration on the sex ratio of land crab (Sesarma haematoche)

Abstract: Adult land crabs generally live on land while their larvae live in the sea. In the case of Sesarma haematoche, female crabs migrate from land to sea to release the larvae at the high tide of syzygy night. Artificial structures along coastal areas are being obstacles for the migration of land crabs and causing synchronized roadkills on coastal roads during breeding migration. In this research, we compared the sex ratios of crab populations in coastal areas with coastal roads and uninhabited island areas with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This result can be explained by the fact that female crabs were disproportionately roadkilled during breeding migration. Importantly, as the crab body size increased, the proportion of females decreased significantly 57 . However, sex ratios of adult land crab were not biased in uninhabited islands 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be explained by the fact that female crabs were disproportionately roadkilled during breeding migration. Importantly, as the crab body size increased, the proportion of females decreased significantly 57 . However, sex ratios of adult land crab were not biased in uninhabited islands 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, as the crab body size increased, the proportion of females decreased significantly 57 . However, sex ratios of adult land crab were not biased in uninhabited islands 57 . As a result, significant male-biased sex ratios of land crab in this study are attributed to female skewed road mortality during spawning migration.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting BCRW simulated a migration of individuals between patches during which they had no choice but to cross the road. This scenario could match many migrating species such as amphibians converging towards open waters for reproduction (Hels & Buchwald, 2001; Sillero, 2008), large mammals migrating to their summer or winter ranges (Avgar et al ., 2014) and crab species moving back to sea during breeding migrations (Ryu & Kim, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…CC-BY-NC 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made during breeding migrations (Ryu & Kim, 2020).…”
Section: Scenario 1: Habitat Fragmentationmentioning
confidence: 99%
“…A study with three different species of freshwater turtles demonstrated more fatalities involving females, due to their seasonal nesting movements along roads (Aresco, 2005). Roadkill rates concentrated in a specific gender can affect demographic structure and influence population dynamics over time (Beaudry et al, 2010; Ryu & Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%